SIMWE model application on susceptibility analysis to bank gully erosion in Alto Douro Wine Region agricultural terraces - Fernandes, J. (2019)
This paper focuses on the susceptibility evaluation to bank gullies on earthen embankments through the applica-tion of SIMWE (SIMulated Water Erosion) model, using a high resolution digital elevation model (1 meter spatialresolution). The results provided by the model are compared with the hydrologic characteristics, soil texture andsoil structure of the agricultural terraces. This approach demonstrates an association between the spatial distri-bution of erosive forms with high values of water depth and reduced water discharge that are consistent withthe lower values of electrical resistivity. The areas with the highest percentage of erosive forms, related to sedi-mentflux, transport capacity and sediment concentration susceptibility, assume medium values. Thesefigures,combined with a low hydraulic conductivity and soil infiltration capacity, are consistent with thefine textureof soils, allowing increased runoff and the development of linear erosion.